Socio-Demographic Factors of Pig Farmers Associated in Transmission of Taeniosis/Cysticercosis - Sharma, Minu (Journal of Institute of Medicine Nepal, 2007)
Background: Pig farmers' socio-economical and environmental conditions that comprise the risk factors for the contraction of cysticercosis in Nepal are as the socio-economic condition of pig farmers is very poor. They are ignorant about health and hygiene. In Terai districts, 80% farmers keep pigs in the open field. Most of the families of the pig rearing communities do not have latrines. They use open field for defaecating. Free range feeding of pig is quite common all over Nepal traditionally. The unhygienic disposal of the waste helps the problem to be graver. Method: This study was carried out in three VDCs i.e. Tindobate VDCs, Thumpokhara VDC, Jagatradevi VDC and Walling Municipality in Syangja district. Household keeping pigs farmers were randomly selected from villages in the district. About 437 households and pig farming area were surveyed. Results: This contamination of soil and water contributes greatly for the parasitic infestation of both pig and human. Most of the pigs are kept inside the house at night and are fed on kitchen wastes and excreta. This is the important factor that is co-related with the high prevalence of parasitic infestations like Taeniasis in pigs and humans. Conclusion: Pig husbandry system should be improved. Mass awareness education programmes for controlling parasitic diseases in general, and taeniasis and cysticercosis in particular should be launched in all pig pocket production areas of the country. Social upliftment programmes like adult education, toilet construction, safe drinking water supply, gender indiscrimination in the pig husbandry as a source of poverty elimination must be carried out. Journal of Institute of Medicine Vol.28(1) 2006